Recovering the tongue: memorializing grieved women through spirit possession and ritual in Zimbabwean literature - Ngoshi, Hazel T. (Taylor & Francis (Routledge), 2016)
In memorializing the past, Zimbabwe’s national and cultural discourses have more often than not drawn their legitimacy from selective versions of past experiences. These discourses are therefore exclusionary or inclusive depending on the cultural and political exigencies of the time. In both national historiography and cultural discourses, the total female experience has not been accounted for. The accounts of the past are fairly homogenized. This article seeks to unravel, in two Zimbabwean fictional narratives, a matrix of authorial endeavours to recover and empower female subjectivity; endeavours that are guided by the tropes of spirit possession, ancestral power and rituals. The article posits that, through spirit possession and the resultant coming to voice of wronged females as well as the authorial elevation of dead women to ancestral status, families and communities engage in integrative processes that facilitate healing and introspection. The focus of the article is on violated womanhood in both the pre-colonial and colonial contexts and in the latter case, with special regard to liberation war experiences in Zimbabwe. The article’s argument is presented within the context of Shona cosmology and the place of spirit possession and ancestral memory therein.